The template synthesis, spectral characterization and thermal behaviour of new binuclear Schiff base complexes derived from N-aminopyrimidine with 2,3-butandion - Sonmez, Mehmet; Sekerci, Memet (Serbian Chemical Soc, 2007)
Anew series of two types of acyclic binuclear Schiff base complexes, prepared by the template condensation of N-aminopyrimidine and 2,3-butandion in the presence of Cu(II), Ni(II), Co(II) and Zn(II) in n-BuOH solution, were analyzed and characterized by elemental analyses, IR and electronic spectroscopy, conductivity and magnetic measurements. From the conductivity measurements, it is concluded that the complex of Ni-II is a 1: 1 type of electrolyte. All the complexes have sub-normal magnetic moments in accordance with their binuclear nature. The thermal behaviour of the complexes was studied by thermogravimetry.
Keywords: acyclic Schiff base complexes; Cu(II); Co(II); Ni(II); Zn(II) template synthesis